(untitled) (Fiep Bulletin - online, 2015)
This article come out from a relevant restlessness related to the preparation of the Physical Education teachers for the teaching profession, bearing in mind the large number of dropouts from the degree courses, the teacher can be one of the reasons the students like and/or dislike school, and the interest and/or lack of interest in the teaching profession. The text is based on a bibliographic research about the subject. The initial graduation introduces the teachers in the world that, in the future, they will be working in, seeking to strengthen their critical and constructive view of knowledge, being followed by the continuing education where the teachers need a constant renewal in their way of thinking, feeling and acting, allowing a transformative education. The teacher graduation is part of the construction of the teacher, the true master builds and rebuilds himself/herself every day.